Risk factors and protective factors in pregnant adolescents - Andreea Giorgiana Mantescu; Diana-Antonia Iordachescu; Elena-Otilia Vladislav; Corina Gica; Anca Maria Panaitescu; Gheorghe Peltecu; Nicolae Gica (Amaltea Medical Publishing House, 2021)
Pregnancy and birth in adolescence involve certain risks for both mother and fetus. Psychologically, adolescent mothers have a higher risk of developing emotional disorders. This paper is a review based on information from the literature. The analysis was limited to articles in English published between January 1, 2000 and September 1, 2021 on PubMed, ScienceDirect and Google Scholar using the following keywords: pregnancy, adolescents, adolescence, risk factors, support factors, psychological interventions. In the context of pregnancy in this challenging stage of adolescence girls should be referred to pre- and postnatal counseling programs or support groups so that they develop healthy relationships and support networks.